Coherent motion of chaotic attractors - Louodop, Patrick [UNESP]; Saha, Suman; Tchitnga, Robert; Muruganandam, Paulsamy; Dana, Syamal K.; Cerdeira, Hilda A. [UNESP] (American Physical Society (APS), 2017)
We report a simple model of two drive-response-type coupled chaotic oscillators, where the response system copies the nonlinearity of the driver system. It leads to a coherent motion of the trajectories of the coupled systems that establishes a constant separating distance in time between the driver and the response attractors, and their distance depends upon the initial state. The coupled system responds to external obstacles, modeled by short-duration pulses acting either on the driver or the response system, by a coherent shifting of the distance, and it is able to readjust their distance as and when necessary via mutual exchange of feedback information. We confirm these behaviors with examples of a jerk system, the paradigmatic Rössler system, a tunnel diode system and a Josephson junction-based jerk system, analytically, to an extent, and mostly numerically.